Nutritional value of the marine fish in Bangladesh and their potential to address malnutrition: A review - Rifat, M. A.; Abdul, Wahab; Rahman, Muhammad; Nahiduzzaman, Md; Mamun, Abdullah-Al (Elsevier, 2024)
Marine fish are good source of essential macro- and micronutrients and major food items in coastal areas in Bangladesh. However, there is no review that details the nutritional value of marine fish in Bangladesh. Therefore, this review focuses on the nutrient composition of marine fish in Bangladesh and how the marine fish can address common nutrient deficiencies among women and children. Nutrient composition data was collected through literature searching in databases and source, including PubMed, Web of Science, Google Scholar, ScienceDirect, WorldFish, and Bangladesh-based database Banglajol. Calculation was carried out to present how one serving marine fish could potentially meet the daily requirement of protein, iron, zinc, calcium, vitamin A, and docosahexaenoic acid (DHA) for pregnant and lactating women and children aged 6–23 months. A total of 97 entries covering nutrient composition analysis of 67 individual fish species were extracted from 12 articles published between 1993 and 2020. Included articles contained analysis of proximate composition, vitamins, minerals, fatty acids, and amino acid. Twelve minerals and nine vitamins were analyzed and reported. The average energy, protein, fat, and ash content per 100 g edible raw marine fish was 343.58 kJ, 16.76 g, 4.16 g, and 2.22 g, respectively. According to available data, marine fish are good sources of protein, zinc, calcium, and DHA. Pelagic small fish, which are mainly captured by artisanal small-scale fishers, had more nutritional value than other categories of fish. Furthermore, marine small fish were found more nutritious than commonly consumed freshwater fish types in Bangladesh, including major carps, introduced carps, and tilapia. Therefore, the study concludes that marine fish have high potential to address malnutrition in Bangladesh. There was scarcity of literature regarding the nutrient composition of marine fish in Bangladesh and in South Asia as a whole, so more comprehensive quality research in this area is recommended.